Relações entre atividades extracurriculares, educação em tempo integral, desempenho escolar, clima familiar e satisfação de vida - Neyfsom Carlos Fernandes Matias (2015)
It is noticed that children and adolescents are influenced by the living of three backgrounds: familial, educational and extracurricular activities. The last one has been drawing the attention of many researches and it is formed by two different ways. The first one is characterized by loss of structure, remaining at home, television watching, play activities, adult supervision usually made by the mother. The second one is linked to structured extracurricular activities (SEAs) frequency, that are related to sports, arts and culture. In Brazil, its frequency has increased due to the Government attempt to implement full-time education. However, there is usually no relationship between the school normal curriculum classes and the SEAs. Therefore, the goal of this study is to investigate the influence of the SEAs over educational achievement, life satisfaction and family environment of students enrolled in the 4th and 5th grades of Brazilian educational system. By means of systematic literature review, it was verified that this theme has not been well addressed by published articles and the few articles found indicate that SEAs effects are not so significant in Brazil. With the use of the review and international literature, three empirical studies were done. The first one investigated the differences between the SEAs participants and non-participants, in a sampling of 78 children, analyzing their educational achievement, the activities structures, and the development of the activities based on participants performance. The outcomes illustrated that children who stay at home, under unstructured activities, demonstrated a superior educational achievement than that of participants of Escola Integrada, a full-time school program made by Belo Horizonte City Government. From these findings, the second study was elaborated in order to adapt a tool to investigate the childrens family environment. 193 students from two different public schools took part of this study. The results of the exploratory factor analysis indicated two elements on the analysis called Family Environment Check List for Children. By means of these two studies, it was possible to write a strategic plan for a third study. Its goal was to identify the differences between SEAs participants and SEAs non-participants, within a sampling of 106 students, according to educational achievement, life satisfaction and family environment. The results didnt show any difference among groups. The explanation for the data found in the first and third studies is SEAs structure and development, as SEAs have an important role of protecting participants and allowing them access to culture and arts. It is concluded that it is necessary to develop a better connection among SEAs and curricular activities, in order to improve the participants educational achievement